THE INFLUENCE OF POSITIVISM PHILOSOPHY ON CRIMINAL LAW ENFORCEMENT IN INDONESIA - Kusumo, Bambang Ali (Faculty of Law, Universitas Sebelas Maret, 2017)
Criminal law enforcement in Indonesia may lack of the justice sense and furthermore highlight the rule of law, this is due to the influence of the philosophy of positivism developed in Europe mainland which has liberal-individualist ideology. This ideology wants everything to be rational and certainty, including legal issues must be no certainty. The purpose of this matter is to protect the rights of individuals. While the Indonesian society is a society that does not highlight the rights of individuals, but respects the balance between individual rights and collective rights. Thus, our criminal law enforcement is still sourced from Indonesian Penal Code which is a replica of the Wetboek Van Strafrech (WVS) created by the Dutch colonialists Government will not materialize justice. It is necessary to face these issues with two steps as the following i.e, first one: the law enforcement agencies in using the law needs a more progressive interpretation, therefore a sense of justice can be realized. Second one, it needs to be realized in accordance with the criminal law reform ideology of kinship based on the values of Pancasila as an ideology of the Indonesia. Such measures are expected to materialize justice in the criminal law enforcement of Indonesia.